Manajemen Pesantren dalam Pembinaan Umat - Hosaini Hosaini; Saeful Kurniawan (Kependidikan Islam Fakultas Agama Islam, 2019)
According to Big Indonesian Dictionary (KBBI) management is the management of the business, the use of management resources. Luther Galick define management as a field of science that systematically seeks to understand why and how people work together to achievegoals. According Zamakhsayari Dhofier is cottage, mosques, students, recitals of classical Islamic books and clerics. Guidance comes from the word